THE EFFECT OF LEADERSHIP, EMPLOYEE PERFORMANCE, MOTIVATION AND INFORMATION TECHNOLOGY ON EMPLOYEE JOB SATISFACTION MODERATED BY AGE OF EMPLOYEES AT DINAS PENANAMAN MODAL DAN PELAYANAN TERPADU SATU PINTU KOTA BEKASI - Pasaribu, Rasnius; Adler Haymans Manurung; Tussoleha Rony, Zahara (Dinasti International Journal of Management Science, 2022)
This research aims to measure the effect of leadership, employee performance, motivation and information technology on employee job satisfaction which moderated by the age of employees at Dinas Penanaman Modal Dan Pelayanan Terpadu Satu Pintu Kota Bekasi. This research is a quantitative research where the object used is all employees who work at Dinas Penanaman Modal Dan Pelayanan Terpadu Satu Pintu Kota Bekasi. The number of samples used as many as 209 respondents. The design used is hypothesis testing using the structural equation model (SEM) – Smart PLS version 3.3.3. The results of this study indicate that: (1) Leadership, employee performance and motivation have a direct effect on employee job satisfaction significantly, (2) There is no direct effect of information technology on employee job satisfaction, (3) Leadership and motivation have no effect on employee job satisfaction if moderated by employee age, (4) Motivation and information technology have a significant effect on employee job satisfaction if moderated by employee age.